Operation of electric machines. Installation of electric machines and transformers - Usmanov Inomjon Israilovich; Mirzayev Islombek; Abdusattarov Akhadjon; Bakhriddinov Oybek (Periodica Journal, 2023)
In this article, opinions were expressed about electrical wiring and transformer assembly
Keywords: asynchronous; generator; stator